Structural characteristics of P123-modified supercritical drying and hydrophobic ambient pressure drying aerogels - Awano, C. M. [UNESP]; Donatti, D. A. [UNESP]; De Vicente, F. S. [UNESP]; Vollet, D. R. [UNESP] (Elsevier, 2013)
Supercritical drying (SCD) and hydrophobic ambient pressure drying (APD) aerogels were prepared from hydrolysis of tetraethoxysilane in solutions of poly(ethylene oxide)-poly(propylene oxide)-poly(ethylene oxide) (P123) in the range of composition below the threshold for the ordered mesoporous silica precipitation. APD was carried out after silylation of wet gels with trimethylchlorosilane (TMCS) or hexamethyldisilazane (HMDZ). The samples were analyzed by small-angle X-ray scattering and nitrogen adsorption. Wet gels are formed by mass-fractal domains, with fractal dimension close to 2, and larger pores superposing the pores belonging to the fractal structure in case of high P123 concentrations. Aerogels exhibit smaller-sized mass-fractal domains with larger mass-fractal dimension accounting for some porosity elimination on drying. The pore volume of the aerogels increases significantly with the P123 amount and it is even larger in the APD aerogels than in the SCD aerogels. © 2013 Elsevier B.V. All rights reserved.
Keywords: HMDZ; Hydrophobic silica; Nitrogen adsorption; SAXS; TMCS; Ambient pressure drying; Ordered mesoporous silicas; Small angle X-ray scattering; Structural characteristics; Drying; Fractal dimension; Gas adsorption; Gels; Hydrophobicity; Nitrogen; Polyethylene oxides; Propylene; Aerogels